Determinan Profitabilitas Perbankan yang Terdaftar di BEI Periode 2018-2020 - Gregorius Ken; Linda Santioso (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This study was conducted with the aim of measuring the effect of capital adequacy ratio, net interest margin, non-performing loan, loan to deposit ratio, operational efficiency ratio on the profitability of banking companies listed on the IDX during the 2018-2020 period using firm size as a control variable. Sample selection is done by using purposive sampling technique. Data processing of 32 banking companies use samples carried out using SPSS Statistics 17 software. The results show that net interest margin has a significant effect on bank profitability, operational efficiency ratio has a significant negative effect on bank profitability, but the ratio of capital adequacy, non-performing loan, loan to deposit ratio does not have a significant effect on the profitability of banking companies.